Agonist bias and agonist‐dependent antagonism at corticotrophin releasing factor receptors - Zoe Tasma; Peter Wills; Debbie L. Hay; Christopher S. Walker (Wiley, 2020)
Abstract The corticotropin‐releasing factor (CRF) receptors represent potential drug targets for the treatment of anxiety, stress, and other disorders. However, it is not known if endogenous CRF receptor agonists display biased signaling, how effective CRF receptor antagonists are at blocking different agonists and signaling pathways or how receptor activity‐modifying proteins (RAMPs) effect these processes. This study aimed to address this by investigating agonist and antagonist action at CRF1 and CRF2 receptors. We used CRF1 and CRF2 receptor transfected Cos7 cells to assess the ability of CRF and urocortin (UCN) peptides to activate cAMP, inositol monophosphate (IP1), and extracellular signal‐regulated kinase 1/2 signaling and determined the ability of antagonists to block agonist‐stimulated cAMP and IP1 accumulation. The ability of RAMPs to interact with CRF receptors was also examined. At the CRF1 receptor, CRF and UCN1 activated signaling in the same manner. However, at the CRF2 receptor, UCN1 and UCN2 displayed similar signaling profiles, whereas CRF and UCN3 displayed bias away from IP1 accumulation over cAMP. The antagonist potency was dependent on the receptor, agonist, and signaling pathway. CRF1 and CRF2 receptors had no effect on RAMP1 or RAMP2 surface expression. The presence of biased agonism and agonist‐dependent antagonism at the CRF receptors offers new avenues for developing drugs tailored to activate a specific signaling pathway or block a specific agonist. Our findings suggest that the already complex CRF receptor pharmacology may be underappreciated and requires further investigation.